Development of regional ethnography in the People’s Republic of Tuva - Anna O. Dyrtyk-ool (Novye Issledovaniâ Tuvy, 2016)
Article reveals the history of formation and development of the regional ethnographic movement in the People’s Republic of Tuva. Regional ethnographic society "Uryankhology”, a role of the first director of the State Museum V.P. Yermolayev, Soviet specialist from Moscow N.M. Bogatyriov are being inquired into.